Behavioural interventions designed to reduce the risk of transmission of Sexually Transmitted Infections (STIs) among university students: current evidence of effectiveness and of potential application at the University of Oxford - Cherneva, L (2017)
Objectives: The overall objective of this thesis was to gain an understanding of behavioural interventions designed to reduce the risk of transmitting Sexually Transmitted Infections (STIs) among university students. In particular, it aimed to: (i) evaluate the effect of those interventions; (ii) understand whether the results of the review are applicable at the University of Oxford; (iii) understand the possible implementation process/processes for sexual health interventions at the University of Oxford. Method: The achievement of the above aims this thesis involved the conduction of a systematic review of randomised controlled trials (RCTs), and a focus group discussion (FGD). Results and further development: Systematic review results showed that the majority of the studies had a low overall risk of bias in the sequence generation aspect and low risk of reporting bias. There was an unclear risk of bias in: allocation concealment, performance bias, detection bias, attrition bias, and bias risk of imbalance between groups at baseline. For further development, this thesis suggest that guidelines such as Consolidated Standards of Reporting Trials (CONSORT) should be followed by researchers in order to improve the quality of reporting, as this would lead to easier and more accurate judgment of the rigours of their work. In terms of the effect of the included studies, only one study measured the intervention’s effect on STI incidence rates (Pedlow 2004). It found no effect on decreasing STI incidence rates at 2-month follow-up. Mixed (and sometimes inconsistent) effects were found for other outcomes, including high-risk behaviours, preventative behaviours, and mediators of behaviour change, with some studies showing an effect and some none. For further development, this thesis recommends conducting a process evaluation in order to see whether the failure of an intervention is due to problems in the theory underpinning the intervention, or simply its delivery. The results of the focus group discussions (FGDs) suggest that there are certain aspects of the interventions that were included in the systematic review that are not applicable at Oxford. These incompatible aspects include specifying population gender, and two outcomes: abstinence from sex, and reducing the number of sexual partners. There were aspects of the interventions which were found applicable to the Oxford setting by the participants, such as the inclusion of sexually active and inactive individuals in the sample. Finally, there were aspects of the interventions that were included in the systematic review which led to contradictory opinions among the participants such as the use of the researcher who designed the intervention as its deliverer. For further development this thesis would recommend recruiting more student representatives from other colleges and societies in order for the results to be more generally applicable. It also recommends more than one focus group session in order to better present the results of the systematic review, and ensure that they are clearly understood by the participants before leading the discussion.